Measurement of the eta_b(1S) mass and the branching fraction for Upsilon(3S) --> gamma eta_b(1S) - Collaboration, TCLEO; Bonvicini, G; Cinabro, D; Lincoln, A; Smith, M; Zhou, P; Zhu, J; Naik, P; Rademacker, J; Asner, D; Edwards, K; Reed, J; et al. (2009)
We report evidence for the ground state of bottomonium, eta_b(1S), in the radiative decay Upsilon(3S) --> gamma eta_b in e^+e^- annihilation data taken with the CLEO III detector. Using 6 million Upsilon(3S) decays, and assuming Gamma(eta_b) = 10 MeV/c^2, we obtain B(Upsilon(3S) --> gamma eta_b) = (7.1 +- 1.8 +- 1.1) X 10^{-4}, where the first error is statistical and the second is systematic. The statistical significance is about 4 sigma. The mass is determined to be M(eta_b) = 9391.8 +- 6.6 +- 2.0 MeV/c^2, which corresponds to the hyperfine splitting Delta M_{hf}(1S)_b = 68.5 +- 6.6 +- 2.0 MeV/c^2. Using 9 million Upsilon(2S) decays, we place an upper limit on the corresponding Y(2S) decay, B(Y(2S) --> gamma eta_b) < 8.4 X 10^{-4} at 90 % confidence level.